2008
DOI: 10.3892/ijo.32.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Ellagitannin-rich pomegranate extract inhibits angiogenesis in prostate cancer in vitro and in vivo

Abstract: Abstract. Angiogenesis is critical to tumor growth and is stimulated by tissue hypoxia due to poor oxygen delivery. In turn, cellular hypoxia leads to angiogenesis via the induction of hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) at a cellular level. Pomegranate juice and extracts, which are rich sources of ellagitannins, have been shown to have chemopreventive potential against prostate cancer, but there have been no studies on the effects of an ellagitannin-rich pomegran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 36 publications
3
79
1
2
Order By: Relevance
“…Pomegranate, consumed as whole fruit, juice, or any form of derivates, possess anti-proliferative, pro-apoptotic, and/or anti-angiogenic effects superior to those observed with their isolated active compounds, suggesting therapeutic strategies that may depart from preference for pure single agents. There are several publications on the anticarcinogenic effects of pomegranate (Ahmed et al, 2005;Jeune et al, 2005;Malik et al, 2005;Syed et al, 2007;Lansky & Newman, 2007;Hajimahmoodi et al, 2008;Jurenka, 2008, Sartippour et al 2008Adams et al, 2010;Adhami et al, 2010;Faria & Calhau, 2010Miguel et al, 2010). Therefore, due to the vast explosion of interest in pomegranate as a functional food and therapeutic source the present work is launched to make a review that highlights anticarcinogenic activity of pomegranate and its products of recently published works.…”
Section: Anticarcinogenic/antitumoral Activitymentioning
confidence: 99%
“…Pomegranate, consumed as whole fruit, juice, or any form of derivates, possess anti-proliferative, pro-apoptotic, and/or anti-angiogenic effects superior to those observed with their isolated active compounds, suggesting therapeutic strategies that may depart from preference for pure single agents. There are several publications on the anticarcinogenic effects of pomegranate (Ahmed et al, 2005;Jeune et al, 2005;Malik et al, 2005;Syed et al, 2007;Lansky & Newman, 2007;Hajimahmoodi et al, 2008;Jurenka, 2008, Sartippour et al 2008Adams et al, 2010;Adhami et al, 2010;Faria & Calhau, 2010Miguel et al, 2010). Therefore, due to the vast explosion of interest in pomegranate as a functional food and therapeutic source the present work is launched to make a review that highlights anticarcinogenic activity of pomegranate and its products of recently published works.…”
Section: Anticarcinogenic/antitumoral Activitymentioning
confidence: 99%
“…5 Pomegranate extract (PE) and its individual polyphenols reveal in vitro and in vivo anticancer effects. 6 PE, containing mainly ellagitannins, shows anti-invasive, antiproliferative, proapoptotic, and anti-inflammatory effects in different cancer cell lines in vitro 7 such as breast cancer, 8 prostate cancer, 9 lung tumors, colon cancer, 10 and skin cancer in mice xenograft models and culture plates. 11 It was found that various PE formulations decreased the proliferation of both types of breast cancer cells which are estrogen-receptor positive and estrogen-receptor negative, 8 in addition to MMTV-Wnt-1 mouse mammary cancer stem cells, 12 mammary organ culture, 13 and moreover decreased the motility and invasion of SUM 149 and MDA-231 cell lines resulting from aggressive cancers.…”
Section: Introductionmentioning
confidence: 99%
“…EA has been found to possess various pharmacological properties as anticarcinogenic, antioxidant, antifibrosis, and chemopreventive properties [9][10][11] . Numerous scientific reports have evaluated the anticancer property of EA both in vivo and in vitro models for various kinds of cancer such as thyroid, breast, prostate, urinary bladder and blood cancer [12][13][14][15] . In spite of these findings, the inhibition of glioblastoma growth by EA has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%